Microbiological profile of bloodstream infections in cancer patients - Sunita Kabi; Bichitrananda Swain; Swati Jain (Wolters Kluwer Medknow Publications, 2021)
Background: Bloodstream infections (BSIs) remain a major cause of mortality in patients with malignancies. Up to 17% of patients who develop a nosocomial BSI in the hospital have an underlying malignancy. Gram-negative bacilli are the predominant etiologic agents of BSI, and their multidrug resistance rate is increasingly being recognized. This study attempts to identify the likely causative agents and their antibiotic susceptibility profile of BSI in cancer patients. Methodology: We conducted a prospective study for a period of 1 year and analyzed the spectrum of BSI and their antimicrobial susceptibility profile in cancer patients. Blood samples were collected aseptically and inoculated in BacT/ALERT (BioMerieux) blood culture bottles. Identification and antimicrobial susceptibility testing of the isolates including their methicillin resistance and β-lactamase and carbapenemase production were done by Vitek-2 (BioMerieux) method. Results: Of a total of 250 cancer patients, 60 (24%) were found to have BSI. The most common underlying malignancy associated with BSI was of gastrointestinal system (45%) followed by acute myeloid leukemia (21.7%). Most of the isolates belonged to Gram-negative bacteria (53.3%). Coagulase-negative Staphylococcus was the most common organism isolated followed by Escherichia coli. Conclusion: The treatment of infections in patients with malignancy relies on the use of established guidelines along with the consideration of local epidemiological data. The poor activity of primary empirical agents and the emergence of multidrug-resistance is alarming.